2015
DOI: 10.1080/09500340.2015.1050471
|View full text |Cite
|
Sign up to set email alerts
|

Passively dual-wavelength Q-switched ytterbium doped fiber laser using Selenium Bismuth as saturable absorber

Abstract: This paper describes a demonstration of a passively dual-wavelength Q-switched ytterbium-doped fiber laser using a selenium bismuth-based saturable absorber. By utilizing a short-length photonic crystal fiber in a ring cavity and performing adjustments to the polarization state of an incorporated polarization controller (PC), we obtained a stable dual-wavelength Q-switched output at 1037.14 and 1037.69 nm, with maximum pulse energy of 0.65 nJ, shortest pulse width of 8.46 μs, and pulse repetition rate from 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The experimental research revealed that the passively Q-switched laser oscillated simultaneously at 1532.32nm and 1556.97nm with a 24.67nm peak separation with a threshold input pump power of 26mW and maximum input pump power of 74mW. The threshold pump power for dual wavelength passively Q-switched is lower than in the research reported in [1,4,11,13] that uses SWNT, BP, Bi 2 Se 3 , and graphene-based SA. The OSA trace is shown in Fig.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…The experimental research revealed that the passively Q-switched laser oscillated simultaneously at 1532.32nm and 1556.97nm with a 24.67nm peak separation with a threshold input pump power of 26mW and maximum input pump power of 74mW. The threshold pump power for dual wavelength passively Q-switched is lower than in the research reported in [1,4,11,13] that uses SWNT, BP, Bi 2 Se 3 , and graphene-based SA. The OSA trace is shown in Fig.…”
mentioning
confidence: 56%
“…The generated pulse produced a maximum peak power and maximum pulse energy of 2.05mW and 11.97nJ, respectively, at maximum input pump power. Figures 6 and 7 show a typical trend of the Q-switched pulse laser as reported by other researchers [1][2][3][4][11][12][13][14], with the advantage of dual wavelength generation. The stability of the generated pulse was further investigated using a radio frequency spectrum analyzer (RFSA) to measure the signal-to-noise ratio (SNR).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…As a result of this, research has now focused on the exploration of new materials for use as SAs. Among the materials being explored are topological insulators (TIs), such as (Bi 2 Se 3 ) [9][10][11][12][13] and bismuth telluride (Bi 2 Te 3 ) [14,15] , which have already seen applications in various Q-switched fiber laser designs. Another potential material is transition metal dichalcogenides (TMDs).…”
mentioning
confidence: 99%